2019
DOI: 10.2334/josnusd.17-0423
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of arthrocentesis with and without hyaluronic acid injection for treatment of temporomandibular joint osteoarthritis

Abstract: This study evaluated the long-term effectiveness of intra-articular temporomandibular joint arthrocentesis for patients with osteoarthritis and compared arthrocentesis/lavage alone with arthrocentesis/lavage and injected hyaluronic acid. Forty patients met the inclusion criteria, and 37 completed long-term follow-up (approximately 4 years). The patients were randomly allocated to two groups: arthrocentesis with lavage alone (A-group, n = 17) or combined with hyaluronic acid treatment (AS-group, n = 20). Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 32 publications
2
40
0
2
Order By: Relevance
“…However, the results of that study cannot be thoroughly evaluated, as one very important issue was omitted, namely, the lavage volume of the perfusate for arthrocentesis was not mentioned in the study. 28 Additionally, we found a significant increase in MMO in the PRP group as compared to the control group -a result which is consistent with that of Cömert Kiliç et al 25 This could be interpreted by the positive impact of growth factors, which restore the viscosity of the synovial fluid and lead to improvement in the jaw movement. On the other hand, we found that although the MMO result in the PRP group was better than in the HA group, there was no significant difference between the MMO values.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the results of that study cannot be thoroughly evaluated, as one very important issue was omitted, namely, the lavage volume of the perfusate for arthrocentesis was not mentioned in the study. 28 Additionally, we found a significant increase in MMO in the PRP group as compared to the control group -a result which is consistent with that of Cömert Kiliç et al 25 This could be interpreted by the positive impact of growth factors, which restore the viscosity of the synovial fluid and lead to improvement in the jaw movement. On the other hand, we found that although the MMO result in the PRP group was better than in the HA group, there was no significant difference between the MMO values.…”
Section: Discussionsupporting
confidence: 90%
“…This effect was not observed by Bergstrand et al, who compared arthrocentesis alone to arthrocentesis with the HA injection. 28 They did not find a statistically significant difference between those groups. However, the results of that study cannot be thoroughly evaluated, as one very important issue was omitted, namely, the lavage volume of the perfusate for arthrocentesis was not mentioned in the study.…”
Section: Discussionmentioning
confidence: 85%
“…The functional and symptomatic improvement in our combined treatment, as shown by numerous researches [17,29,33,34], appears to be linked to:…”
Section: Discussionmentioning
confidence: 65%
“…Based on this consideration, as proposed by other authors [32,33], the technique analyzed in our research used a combined approach in which the effect of the intracapsular administration of SH was added to the action of the arthrocentesis and the repetition of a cycle of 5 injections (1 per week). In the patient enrollment criteria for this study, we used both the DC/TMD classification system and the Wilkes staging system for TMJ internal derangement stages.…”
Section: Discussionmentioning
confidence: 99%
“…Arthrocentesis coupled with viscosupplementation proved efficient in relieving symptoms associated with Tmj/ OA. Arthrocentesis was long advocated for its effectiveness on clearing the joint from all inflammatory mediators and cytokines aiming to regain intraarticular homeostasis [12] as well as eliminating intraarticular effusion, reducing pain and minimizing loading effect on the joint which aids in preserving joint movements [13] .…”
Section: Introductionmentioning
confidence: 99%